The Possibilities of the Russian Regions Capacity Increasing Under the External Threats - Matveyeva, Lyudmila Grigoryevna; Mikhalkina, Yelena Vladimirovna; Chernova, Olga Anatolyevna (Economy of Regions, 2015)
Managing of using and developing the Russian regions potential under the terms of economic sanctions from foreign countries require prior modeling of the results of decisions made to identify the most significant areas of management actions. The main aim of the paper is to study the possibilities of cognitive modeling methods in the process of assessing the consequences of external threats to regional economies and the subsequent generation of solutions that are foreground in the terms of regions total potential increasing. On the basis of developed cognitive model, the analysis of interconnected impulsive processes in managing the region's economic potential was made, which demonstrates the possibilities of using this model to predict the possible trends of development of the situation within the implementation of the specific management decisions. Sequence of the procedures conducted in the framework of the model allows to define the priority and the importance of the impacts on the development of the region's internal potential under the external threats. As well as to assess the necessity and adequacy of the stimulating and regulatory management measures application, due to the changes of the key factor of the model in order to prevent undesirable changes of the target factors and, in contrary, to improve them. Presented tool is universal and can be adapted to the specific regional conditions and specific “threats.”